Analysis of The Fufillment of the Rights to Remission for Correctional Students at the Class 1 Special Child Develpoment Institution in Palembang - KHUSNUL KHOTIMAH; Yuslistia Opeska; Agustin Wela Sasih; Ridwan Santoso (UNIVERSITAS PGRI YOGYAKARTA, 2026)
This study examines the fulfillment of remission rights for correctional inmates at the Class I Palembang Correctional Institution (LPKA). The study aims to analyze the implementation of remissions and the obstacles encountered in their implementation. The study was conducted at the Class I Palembang Correctional Institution using empirical legal research methods and a qualitative approach. Data collection techniques included interviews, observations, and documentation studies. The results indicate that the implementation of remissions is essentially in accordance with Law Number 22 of 2022 concerning Corrections, Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, and Regulation of the Minister of Law and Human Rights Number 16 of 2023. However, its implementation still faces administrative obstacles, limited staff understanding of the latest regulations, and the suboptimal implementation of the Prisoner Development Assessment System (SPPN). Therefore, it is necessary to increase the capacity of staff and optimize the development system so that the fulfillment of remission rights can be carried out more effectively and oriented towards the best interests of children.